The Winter witch - Brackston, Paula (St. Martin's Press, 2013)
Mute fledgling witch Morgana is married for her safety to a kind farmer in the mountains of Wales before she is targeted by townspeople who are being manipulated by a dark force that compels Morgana to harness her powers.